Dinamika Hukum Penangguhan Upah Minimum Kabupaten/Kota Bagi UMKM dalam Perspektif UU Cipta Kerja - Savira, Karina Amanda; Kurniawan, Angga (Muhammadiyah Law Review Journal, 2025)
This study aims to identify and analyze the legal certainty, benefits, and fairness for employers and workers following the provision to abolish the article on postponing minimum wages at the city and/or regency levels in Law Number 11 of 2020 on Job Creation. Another objective of this study is to examine and analyze the effectiveness of the implementation of the abolition of the article on postponing minimum wages at the city and/or regency levels in the business sector under Law Number 11 of 2020 on Job Creation.This research employs a normative-empirical approach with a descriptive-analytical nature. The study involves library research to collect secondary data through document studies on primary and secondary legal materials. Field research was also conducted to obtain primary data through interviews with key informants and respondents, using interview guidelines as the instrument. The research findings from both library and field studies were then qualitatively analyzed and presented descriptively.The provision to abolish the article on postponing minimum wages at the city and/or regency levels in Law Number 11 of 2020 on Job Creation provides legal certainty, benefits, and fairness for employers and workers because the abolition of the article does not violate existing regulations. Using the legal certainty theory approach, the regulation on the abolition of the article on postponing wages in Law Number 11 of 2020 on Job Creation is considered to meet the criteria outlined in legislation. However, the theories of benefits and fairness have yet to be fully realized, as further field research is required to address the second problem. Secondly, the effectiveness of implementing the abolition of the article on postponing minimum wages, except for micro-enterprises, in Law Number 11 of 2020 on Job Creation